High mobility group box transcription factor 1 (HBP1) from Lampetra japonica affects cell cycle regulation. (8th March 2018) - Song, Xiaoping; Gao, Xingxing; Lu, Jiali; Liang, Hongfang; Su, Peng; Li, Qingwei; Pang, Yue
Abstract: High mobility group (HMG) box‐containing protein 1 (HBP1) is a member of the HMG family of chromosomal proteins. Previous studies have shown that human HBP1 exhibits tumor‐suppressor activity. Here, we identified a homologue of HBP1, L‐hbp1, in Lampetra japonica . The L‐hbp1 gene shared high sequence similarity with its homologues in jawed vertebrates, as shown by bioinformatics analyses. L‐hbp1 contains a 1, 584‐bp open reading frame that encodes 527 amino acids. A pAdenox‐L‐HBP1 plasmid was constructed and transfected successfully in Raji cells, as revealed by real‐time PCR. The overexpression of L‐HBP1 reduced cell growth rates, inhibited G1 phase progression, decreased cyclin D1 and c‐Myc protein expression, and increased p53 protein expression. Western blot and immunohistochemical assays showed that L‐HBP1 was primarily distributed in the heart, kidney, gill and liver of lamprey. Cell cycle analysis revealed that decreased L‐HBP1 expression in HBP1 morpholino oligonucleotide‐transfected lamprey cells resulted in a decreased fraction of cells in the G1 phase and corresponding increases in the S and G2/M phases. Additionally, treatment of lamprey cardiac cells with pharmacological inhibitors of p38 MAP kinase released the cells from G1 arrest. Together, these results indicated that HBP1 expression in lamprey was correlated with the onset of mitotic arrest in these cells, which have implications for cell cycle regulation. Abstract : hbp1 expression in lamprey cells appears to correlate with the onset of mitotic arrest in these cells, which has implications in cell cycle regulation.